Investigation of the Partial Volume Effect in Pre-Dosimetry of Liver Tumors for 90 Y Radioembolization: A Phantom Study - Dilaver Akar, Ayşe; Yeyin, Nami; Akyol, Sinem; Demir, Özge; Gülce Çoker, Eylem; Demir, Mustafa (Molecular imaging and radionuclide therapy, 2025)
Yttrium-90 ( Y) radioembolization has become increasingly important in the treatment of liver tumors. This study aims to experimentally determine the extent to which small liver tumors are affected by the partial volume effect (PVE) in single photon emission computed tomography/computed tomography (SPECT/CT) scintigraphy using technetium-99m-macroaggregated albumin (Tc-99m-MAA), and to investigate the impact of PVE on tumor dosimetry and image quality. In this experimental study, a custom-designed liver phantom containing four tumor mimics with diameters of 1 cm, 2 cm, 3 cm, and 5 cm was used. The tumor and liver parenchyma volumes were filled with Tc-99m at a ratio of 4.86: 1. The phantom was imaged in a water tank using SPECT/CT according to standard clinical protocols. Volumetric regions of interest were drawn for each lesion and tumor volumes, contrast values (C), contrast to noise ratios (CNR), and absorbed tumor doses were calculated from the counts obtained. Since this study does not involve live subjects and was conducted solely on a phantom model, ethical approval, informed consent, and consent forms are not required for this study. Tumor diameters measured on SPECT/CT images matched those obtained from both CT images and the actual dimensions. The contrast values calculated from the SPECT/CT images for lesions with diameters of 2 cm and 5 cm were 2.03 and 3.89, respectively. Similarly, the corresponding CNR values were 8.64 and 21.07. Tumor-to-normal tissue ratios were 2.03 and 3.89 for the 2 cm and 5 cm lesions, respectively. For the 2 cm lesion, the actual and SPECT/CT-derived absorbed doses were 15.3 Gy and 7.87 Gy, respectively. For the 5 cm lesion, these values were 15.4 Gy and 13.38 Gy, respectively. the absorbed tumor doses significantly decreased as tumor diameter decreased due to the influence of PVE. Tumors smaller than 2 cm in diameter were markedly affected by the PVE. Considering the influence of PVE, or applying appropriate corrections in dosimetric calculations, is of critical importance for improving the accuracy of dosimetry results.